2023
DOI: 10.1111/psyg.13000
|View full text |Cite
|
Sign up to set email alerts
|

Does surgery cause anxiety, stress and fear in geriatric patients?

Abstract: BackgroundBecause of physiological changes in geriatric patients, their surgical process differs from that of young adults. In this regard, the perioperative period is an extremely risky time for geriatric patients. The present study examined preoperative fear, anxiety, and perceived stress levels as well as the factors affecting them in elderly patients prior to surgical intervention.MethodsThis study adopted a cross‐sectional descriptive design. The study sample consisted of geriatric patients (n = 407) sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In support of this idea, a study reported that patients with social support had significantly lower preoperative anxiety levels compared to those without social support. 26 Karabulut et al 16 also reported that the level of surgical fear in geriatric surgical patients who were married was lower than in those who were single. Additionally, Tesfaw et al 27 mentioned that preoperative anxiety levels were twice as high in single individuals compared to married ones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In support of this idea, a study reported that patients with social support had significantly lower preoperative anxiety levels compared to those without social support. 26 Karabulut et al 16 also reported that the level of surgical fear in geriatric surgical patients who were married was lower than in those who were single. Additionally, Tesfaw et al 27 mentioned that preoperative anxiety levels were twice as high in single individuals compared to married ones.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 The reason for these differences in studies may be due to the 75 and above undergoing laparoscopic cholecystectomy, while they were low in patients aged 65-69. 16 In the study by Kapıkıran and colleagues, it was determined that the highest level of surgical fear in patients undergoing abdominal surgery was observed in individuals aged 65 and above. 22 In this study, the long-term fear level of elderly patients who were married was statistically significantly lower (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A preliminary study conducted among 65 patients awaiting cardiac surgery provided promising results regarding the reliability of the scale (Cronbach's a coefficient for the full scale was 0.93, for short-term aspects of surgery was 0.91, and for long-term surgery aspects was 0.90). The SFQ questionnaire has been used in studies conducted in the Netherlands [28,29], Greece [34], Portugal [35,36], Turkey [21,23,33,[37][38][39][40][41][42][43], Croatia [44], Norway [45], Germany [31], Italy [46], Czech Republic [30], China [32], United States [47,48], Ireland [49], and Hungary [50][51][52]. Most of these publications appeared in the years 2022-2023.…”
Section: Prospective Evaluation Monitoring the Level Of Anxietymentioning
confidence: 99%
“…The fear of the unknown, loss of control, and potential risk of harm all contribute to this anxiety-inducing situation (3,4). Several studies demonstrated that physical stress, psychological stress, stress due to hospitalization, self-care stress, and spiritual stress are the main sources of stress experienced by patients who are candidates for various surgery that result in enhancing the risk of complications, morbidity, and mortality (5)(6)(7)(8)(9)(10)(11). A situation is stressful when it is perceived by a person as threatening and uncontrollable and that person does not have the necessary resources to face the situation (12).…”
Section: Introductionmentioning
confidence: 99%